2022
DOI: 10.3390/ma15175866
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Marginal Bone Loss Progression on Stress Distribution in Different Implant–Abutment Connections and Abutment Materials: A 3D Finite Element Analysis Study

Abstract: Peri-implantitis is a common implant-supported prosthesis complication, and marginal bone loss affects the stress distribution in implant systems. This three-dimensional finite element analysis study investigated how bone loss affects the implant assembly; in particular, models including two implant systems with different connection systems (external or internal hexagon), abutment materials (titanium or zirconia), and bone loss levels (0, 1.5, 3, or 5 mm) were created. We observed that the maximum von Mises st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 44 publications
0
0
0
Order By: Relevance
“…Titanium implants, while studies comparing different materials for craniofacial reconstruction are still limited, appear to be associated with increased donor site comorbidity, including bone resorption [35]. Countless studies have demonstrated that implants crafted from specific materials, such as titanium alloys, may induce peri-implant bone resorption attributable to stress shielding phenomena [36,37]. Stress shielding is a biomechanical phenomenon that leads to adaptive changes in bone strength due to the altered distribution of physiological loads on the bone, potentially leading to implant loosening.…”
Section: Prostheses Can Lead To Underlying Bone Resorptionmentioning
confidence: 99%
“…Titanium implants, while studies comparing different materials for craniofacial reconstruction are still limited, appear to be associated with increased donor site comorbidity, including bone resorption [35]. Countless studies have demonstrated that implants crafted from specific materials, such as titanium alloys, may induce peri-implant bone resorption attributable to stress shielding phenomena [36,37]. Stress shielding is a biomechanical phenomenon that leads to adaptive changes in bone strength due to the altered distribution of physiological loads on the bone, potentially leading to implant loosening.…”
Section: Prostheses Can Lead To Underlying Bone Resorptionmentioning
confidence: 99%
“…Factors influencing this phenomenon include not only the material but also the design, mechanical loading, and notably, the interface between the implant and the periosteum. Titanium implants, while studies comparing different materials for craniofacial reconstruction are still limited, appear to be associated with increased donor site comorbidity, including bone resorption [39]. Countless studies have demonstrated that implants crafted from specific materials, such as titanium alloys, may induce peri-implant bone resorption attributable to stress shielding phenomena [40,41].…”
Section: Prostheses Can Lead To Underlying Bone Resorptionmentioning
confidence: 99%
“…Both phenomenons lead to failure of implant restorations [21][22][23]. There are several publications investigating the mechanical behaviors of the implants with the Finite Element Analysis (FEA).…”
Section: Osseointegration and Its Influencing Factorsmentioning
confidence: 99%
“…In the study of Lin et al, a FEA method was to investigate the type of contact between implant and peri-implant hard tissues for which the distribution of masticatory forces is more uniform. They found that the von Miss stress distribution is most uniform for the tapered connection implant -abutment [22].…”
Section: Osseointegration and Its Influencing Factorsmentioning
confidence: 99%